2016
DOI: 10.1039/c5cp06463e
|View full text |Cite
|
Sign up to set email alerts
|

Alcohols at the aqueous surface: chain length and isomer effects

Abstract: Surface-active organic molecules at the liquid-vapor interface are of great importance in atmospheric science. Therefore, we studied the surface behavior of alcohol isomers with different chain lengths (C4-C6) in aqueous solution with surfaceand chemically sensitive X-ray photoelectron spectroscopy (XPS), which reveals information about the surface structure on a molecular level. Gibbs free energies of adsorption and surface concentrations are determined from the XPS results using a standard Langmuir adsorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
73
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 46 publications
8
73
1
Order By: Relevance
“…Measurements are made at room temperature using different experimental methods, including (i) neutron reflection (Li et al, ), (ii) mass spectrometric probing of molecular clusters, presumably in equilibrium in the headspace above a liquid surface (Raina et al, ), and (iii) analysis of experimental surface tension data based on Gibbs' adsorption equation (equation ; Li et al, ). Together with (iv) X‐ray photoelectron spectroscopy (XPS; Walz et al, ), these methods have been used to probe the composition and thickness of water‐ n ‐butanol surfaces. There are quantitative differences between the results obtained from the different measurements; however, considering the complex nature of the experiments, the qualitative agreement (numerically within about a factor of three) is quite reasonable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Measurements are made at room temperature using different experimental methods, including (i) neutron reflection (Li et al, ), (ii) mass spectrometric probing of molecular clusters, presumably in equilibrium in the headspace above a liquid surface (Raina et al, ), and (iii) analysis of experimental surface tension data based on Gibbs' adsorption equation (equation ; Li et al, ). Together with (iv) X‐ray photoelectron spectroscopy (XPS; Walz et al, ), these methods have been used to probe the composition and thickness of water‐ n ‐butanol surfaces. There are quantitative differences between the results obtained from the different measurements; however, considering the complex nature of the experiments, the qualitative agreement (numerically within about a factor of three) is quite reasonable.…”
Section: Resultsmentioning
confidence: 99%
“…Toribio et al () reported surface enrichment factors for aqueous n ‐butanol, modeled from a statistical mechanics based surface model (Boyer et al, ; Wexler & Dutcher, ), which are of similar magnitude albeit somewhat smaller, compared to the present monolayer model. Curiously, Toribio et al () find similar discrepancies of about a factor of 3 between their model predictions and experimental XPS‐derived surface concentrations of aqueous alcohols (Walz et al, ). This comparison was however done for n ‐butanol concentrations an order of magnitude higher than in the studies compared in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes 32 Here, c s,max was estimated by choosing a value that successfully reproduced surface tension data of pure SuccH 2 solutions.…”
mentioning
confidence: 99%